Evaluation of in vitro Antioxidant Activity and total Phenolic content of Methanol Bark Extract of Mimusops elengi - Rao, K. Srinivasa; Munjuluri, Prameela Rani; Kumar, B.V.V. Ravi; Keshar, Nargesh K. (Free Radicals and Antioxidants)
Introduction: Some researchers suggest that two-thirds of the world’s plant species have medicinal value; in particular, many medicinal plants have great antioxidant potential. Antioxidants reduce the oxidative stress in cells and are therefore useful in the treatment of many human diseases, including cancer, cardiovascular diseases and inflammatory diseases. Methods: The present study was projected to evaluate the in vitro potential of methanol extract of Mimusops elengi bark in correlation to the ascorbic acid which was used as a reference standard. The antioxidant properties of methanolic extract that probably involve free radical mechanisms were evaluated by the methods namely DPPH, ABTS, Hydroxy radical and Nitric oxide radical Scavenging assays. Results: The IC50 values of methanol extract in DPPH radical, nitric oxide, ABTS radical and hydroxyl radical were obtained to be 2.2 μg/ml, 158.49 μg/ml, 7.69 μg/ml and 3 μg/ml respectively. However, the IC50 values for the standard ascorbic acid were noted to be 0.66 μg/ml, 200 μg/ml, 0.7 μg/ml and 1 μg/ml respectively. Measurement of total phenolic content of the methanol extract of M. elengi was achieved using Folin– Ciocalteau reagent containing 698.7 ± 0.93 mg/g of phenolic content, which was found signicantly higher when compared to reference standard gallic acid. Conclusions: The observed results clearly indicate that M. elengi has a significant anti-oxidant activity and the results correlate positively with total phenol content strongly plead in favour of the use of this plant as potential food additives in replacement of synthetic compounds.
Keywords: Mimusops elengi; Anti-oxidant activity; Total Phenolic content; Methanol bark extract